PENGARUH PEMBERIAN EKSTRAK KEMANGI (Ocimum sanctum) TERHADAP JUMLAH SARAF NITRERJIK DI HIPOKAMPUS PROPER TIKUS PUTIH (Rattus norvegicus) - , ANTONIUS GRATUS M ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Brain is a multifunctional organ, one of which is for memory and learning abilities. The hippocampus is the part of the brain which responsible for memory and learning abilities. Itâs consist s of three parts which are subiculum, hippocampus proper, and gyrus dentatus. Various nootropic agents such as piracetam and aniracetam are used to increase the memory capability. However these agents have side effects. Nitric oxide (NO) is a neurotransmitter involved in memory and learning. Basil is an Indonesian herb used to improve memory and learning abilities. The purpose of this research is to determine the influence of basil extract to the quantity of nitrergic nerve in hippocampus proper. This study uses 9 Sprague-Dawley male rats aged 4 weeks with a body weight of 50-60 g. Each rat was treated using basil extract at a dose of 4 mg / kg / day. At two, six, and eight weeks of treatment, 3 rat anaesthetized with ketamine dose of 100 mg / kg and xylazine 10 mg / kg, intracardialy perfused with 0.9% NaCl and fixated in 4% phosphate buffer formalin. Taken in the hippocampus area of the brain for making histological preparations with cryostat sections 20 Âµm, and stained with Haematoxylin Eosine and Nicotinamide Adenine Dinucleotide Phosphate-diaphorase (NADPH-d). The result showed that there was a nerve cells stained in triangular and round shapes in cornu ammonis. Number of nerve cells and nitrergic nerve cells in the cornu amonis rat increases with age. The percentage of nitrergic nerve at 2 weeks, 6 weeks and 8 weeks extract basil treatment in the CA1 area were 17,78%, 19,16%, and 20,53% respectively